Analisis Kemampuan Berpikir Kreatif Siswa dalam Pembelajaran IPA Melalui Model Project Based Learning di SDN 2 Talise - Siwi Astuti Tri Rudiani Rudiani; Yusdin Bin Mahmudin Gagaramusu; Azizah Azizah; Sri Wahyuni (JURNAL DIKDAS, 2025)
This study aims to determine students' ability to think creatively in science learning through the Project Based Learning model for grade V students of SDN 2 Talise. This study uses a type of qualitative research, the subjects in this study are fifth grade teachers and students. The instruments in this study were observation sheets, interviews and documentation. The results of this study indicate that the application of the Project Based Learning learning model for grade V students of SDN 2 Talise in science lessons with ecosystem material and making ecosystem dioramas is able to have a positive impact on the material that has been delivered. In the learning process students are easier to understand the material that has been delivered and in the learning process students are able to develop fluency thinking skills (fluency), flexible thinking skills (flexibillity), originality thinking skills, and detailed thinking skills (elaboration).